Anglican theology: postcolonial perspectives - Burns, Stephen; Tengatenga, James (London: SCM Press, 2024)
"It is now widely acknowledged that Anglicanism, far from being centred on western contexts is a worldwide phenomenon, with some of its liveliest corners located in the global south. Yet the Anglican theology which is taught in institutions is still focused overwhelmingly on a handful of British and North American voices. By exploring the work of eighteen tricontinential and marginalized Anglican theology towards Britain and North Atlantic contexts. The chapters it gathers considers the methods, concerns and contributions to Anglican thinkers from Africa, Asia, Pasifika, South American and eastern European settings, amongst minoritized migrants to North Atlantic countries"--Page 4 of cover
ContributorsIntroduction: Worthy of God$1 (Bs Trust? | Stephen Burns and James Tengatenga1 Denise Ackerman | Jenny Te Paa-Daniel 2 Naim Ateek | Yazid Said3 Mukti Barton | Michael N. Jagessar4 Burgess Carr | Herman Browne5 Verna Dozier | Karen Meridith6 Julius Gathogo | Stephen Kapinde7 Winston Halapua | Frank Smith8 Kwok Pui-lan | Keun-joo Christine Pae9 Jaci Marischin | Carlos Eduardo Calvani10 John Mbiti | Henry Mbaya11 Jesse Mugambi | Julius Gathogo12 Nyameko Barney Pityana | James Tengatenga13 John Acland Ramadhani | Patrick Bendera, Maimbo W. F. Mndolwa & Fergus J. King14 Harry Sawyerr | Herman Browne15 Jenny Te Paa-Daniel | Esther Mombo16 Miroslav Volf | George Sumner17 Gerard O. West | Cynthia Briggs Kittredge18 Gale A. Yee | Stephen Burns Afterword | Peniel Rajkumar Appendix | Suggested further readings
Includes bibliographical references and index.
Keywords: Anglican Communion -- Doctrines; Anglican Communion -- Theologies; Postcolonial theology